How does rising house price influence stock market participation in China? A micro-household perspective - Xiaoyu Chen; Xiaohao Ji (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
This is an empirical study on the effect of house price on stock-market participation and its depths based on unique China Household Finance Survey (CHFS) data in 2011 and 2013 including 36213 sample households. We mainly found that, with an increase of one thousand RMB per square meter in macro house price, the probability to participate in the stock market will increase by 5.4% before controlling for wealth effect and 2.84% afterwards, indicating the existence of wealth effect. The participation depths of the stock-total asset ratio is expected to decrease by 0.23% and absolute stock asset is observed to decrease by 5.8 thousand RMB in response to one thousand RMB increase of per square meter house price. The effect of house price on participation decision is also related to housing area, and the negative effect of house price on stock market participation depths gets more intense with the increase of the stock-total asset ratio.
Keywords: D13; G11; R21; R32; 330; stock market; participation decision and depth; house price; China; CHFS data